UTILIZATION OF YOUTUBE VIDEO AS A THEMATIC LEARNING MEDIA IN ELEMENTARY SCHOOL - Febrin Lutftia Anastasya; Muhammad Afandi; Aquami Aquami; Tutut Handayani; Nurlaeli Nurlaeli (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to describe the application of YouTube media, the inhibiting and supporting factors, and their impact on students in thematic learning at fourth-grade at State Elementary School (SDN) 35 Prabumulih. This research method is mixed method. Data collection techniques through interviews, observation, documentation, and questionnaires which tested validity and reliability. Qualitative data analysis techniques through data reduction, data presentation, and concluding. Quantitaive data is analyzed in the frequency distribution table. The results showed that the implementation of YouTube media in thematic learning at fourth-grade SDN 35 Prabumulih was carried out through preparation activities, presentation of material, questions and answers about videos that were displayed, and follow-up. The supporting factors are, YouTube easier for students to learn, a strong and stable signal, and the facilities and infrastructure presented by the school. While the inhibiting factors are the internet signal which is sometimes unstable, the availability of facilities and infrastructure is still limited and not functioning properly, and the extravagant of internet data usage. The use of YouTube media in thematic learning has a positive impact on the student learning process because it can offer a varied and fun learning atmosphere, and stipulate a better conceptual understanding related to knowledge (cognitive); remembering, conceiving, and applying.